Impact of COVID-19 on pregnant women in South Korea: Focusing on prevalence, severity, and clinical outcomes. Issue 2 (February 2022) - Kim, So Hee; Choi, Yeonmi; Lee, Dokyoung; Lee, Hyejin; Kim, Ji Hoi; Choi, Eun Saem; Jung, Young Mi; Lee, Jinwoo; Choe, Pyoeng Gyun; Lee, Ji Yoon; Do, Youngme; Park, Chan-Wook; et al.
Abstract: Background: In the era of coronavirus disease 2019 (COVID-19) pandemic, there is a paucity of information regarding actual prevalence of COVID-19 in pregnant women compared to non-pregnant women. The purpose of this study was to investigate the prevalence of COVID-19 infection and clinical outcome in pregnant women and non-pregnant women. Methods: This is a nationwide cross-sectional study in South Korea between January 2020 and February 2021 using the claim database. The primary outcome was the prevalence of COVID-19 in pregnant women, and the secondary outcome was the occurrence of severe COVID-19 illness among infected patients. Severity of COVID-19 was classified into four categories according to WHO ordinal scale. Results: The prevalence of COVID-19 infection was lower in pregnant women than non-pregnant women aged 20–44 (0·02% vs. 0.14%, p < 0.0001). However, among COVID-19 positive women at age 20–44, pregnant women was at higher risk of oxygen therapy after hospitalization (score 4 in WHO ordinal scale: 6.4% vs. 1.6%, p < 0.05). There were no deaths or hospitalized severe disease in pregnant women with COVID-19, although the majority of them (96·2%) were admitted to hospital. On the other hand, 42·3% of non-pregnant women at 20–44 age were admitted to hospital and 0.04% of them died and 0.1% had hospitalized severe disease. Conclusions: The prevalence of COVID-19 infection in pregnant women was lower than non-pregnant women in Korea, resulting in relatively small cases of fatality. It has implications that public health policy, such as an effective response to COVID-19 and a powerful preemptive strategy for pregnant women, can lower risk of COVID-19 infection and better clinical outcomes in pregnant women with COVID-19.